THE CUSTOMER LOYALTY RESEARCH TRENDS: BIBLIOMETRY ANALYSIS - Basrowi Basrowi; Juhary Haji Ali; Tulus Suyanto (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
This research is a systematic mapping in the topic of Customer Loyalty (CL) studies based on bibliometric analysis. The purpose of this study was to find out how the development of citations, publication trends, collaboration of authors, trends in title terms, trends in keyword terms in Customer Loyalty (CL) articles during the last ten years 2013-2022. Data collection using publish or perish (PoP) software in bibliographic search as the initial database on Google Schoolar and Scopus. The results showed that from 500 papers, the number of citations reached 38813 citations, with an average annual citation of 4312.56 citations, 77.63 citations per paper, and an average h-index of 113. The highest fifteen citations with authors from various countries collaborate, the top three are; P Martínez, IR Del Bosque (1059 citations) publisher Elsevier; J Kandampully, TC Zhang, A Bilgihan (664 citations) emerald publisher, and A Bilgihan (635 citations) emerald publisher. Of the top fifteen articles dominated by publisher elsevier, emerald, and springer. More deeply, the results of the VOSviewer analysis found that there were 39 items with 10 (ten) clusters related to the field of consumer loyalty. Cluster 1 (6 items) are Airline industry, Case study, Customer loyalty, Customer loyalty program, Customer relationship, and customer retention. Cluster 2 (4 items) consists of Corporate reputation, CSR, Customer trust, and Moderating role. Cluster 3 (3 items) includes Brand, Intention Moderating Effect, and Relationship quality. Cluster 4 (2 items) consists of Customer engagement and Customer experience. Cluster 5 (2 items) are Loyalty program and Relationship marketing. Cluster 7 (2 items) namely Empirical study and Reputation. Cluster 8 (2 items) namely Commitment and Customer value. Cluster 9 (2 items) namely Factor and Importance. It can be concluded that the study of the science of loyalty is connected with other additional factors that are taken into account. Therefore, it is very important for future studies to develop 10 (ten) clusters related to consumer loyalty to understand consumer behavior as the key to business success in the era of the industrial revolution 4.0